SHAPING PREFERENCES OF MARKET ENTITIES IN THE AGE OF DIGITALIZATION - Brol, Marcin; Czetwertyński, Sławomir (Ekonomia i Prawo. Economics and Law, 2013)
The aim of this paper is to answer the question: are the actors of the new public sphere influencing preferences of all market entities or are they only part of society with universal preferences? Authors tend toward the view that we are observing decline of traditional public sphere and building of new – virtual public sphere, with different forms of relations between actors of this sphere. The actors are now independent of time, place and social status.